Relationship between coping strategies, dimensions of burnout syndrome and life quality in medical students - Rafaella do Carmo Ribeiro, Milena Nunes Alves de Sousa (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v9i0.9151